Hipotensión ortostática en enfermedad de Parkinson - Gómez R., Rodrigo; Hudson R., Lorena; Venegas F., Pablo; Guerrero B., Sofía; Silva C., Consuelo; Riquelme M., Ximena (Revista Hospital Clínico Universidad de Chile, 2011)
The current concept of Parkinson’s disease comprises a group of non-motor symptoms: neuropsychiatric disorders, sleep disturbances and dysautonomia, among others. Orthostatic hypotension is a frequent problem that impairs the patient’s quality of life. We review the symptoms of this disorder, its pathogeny and the available diagnostic tools. We emphasize the early suspicion and show the treatment options, based on the available evidence and our experience.